Nutritional Evaluation of Commercially Important Fish Species of Lakshadweep Archipelago, India - Dhaneesh, Kottila Veettil (Public Library of Science, 2012)
Estimation of nutrition profile of edible fishes is essential and thus a bio-monitoring study was carried out to find out the nutritional composition of commonly available fishes in Agatti Island water of Lakshadweep Sea. Protein, carbohydrate, lipid, ash, vitamin, amino acid and fatty acid composition in the muscle of ten edible fish species were studied. Proximate analysis revealed that the protein, carbohydrate, lipid and ash contents were high in Thunnus albacares (13.69%), Parupeneus bifasciatus (6.12%), Hyporhamphus dussumieri (6.97%) and T. albacares (1.65%), respectively. Major amino acids were lysine, leucine and methionine, registering 2.84–4.56%, 2.67–4.18% and 2.64–3.91%, respectively. Fatty acid compositions ranged from 31.63% to 38.97% saturated (SFA), 21.99–26.30% monounsaturated (MUFAs), 30.32–35.11% polyunsaturated acids (PUFAs) and 2.86–7.79% branched fatty acids of the total fatty acids. The ω-3 and ω-6 PUFAs were ranged 13.05–21.14% and 6.88–9.82% of the total fatty acids, respectively. Hence, the fishes of Lakshadweep Sea are highly recommended for consumption, since these fishes are highly enriched with nutrition. The results can be used as a baseline data for comparing the various nutritional profiles of fishes in future.